2006
DOI: 10.1038/emm.2006.54
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of nicotinamide N-methyltransferase in gastric cancer tissues and its potential post-translational modification

Abstract: Gastric cancer is one of the most common cancers worldwide. The purpose of this study was to find out potential markers for gastric cancer. Tumor and normal tissues from 152 gastric cancer cases were analyzed by two-dimensional gel electrophoresis (2-DE). The images of silver stained gels were analyzed and statistical analysis of spot intensities revealed that spot 4262 showed higher expression (5.7-fold increase) in cancer tissues than in normal tissues (P <0.001). It was identified by peptide mass fingerprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 24 publications
2
69
0
Order By: Relevance
“…These results indicated that NNMT promoted EMT in gastric cancer cells mainly by upregulating TGF-β1 expression. It has been demonstrated that NNMT-mediated methylation is an important conjugation reaction in the biotransformation of a number of drugs and xenobiotics, including pyridine and other structurally-associated compounds (18). The epigenetic silencing of TGF-β1 genes is associated with the development of pituitary adenoma (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that NNMT promoted EMT in gastric cancer cells mainly by upregulating TGF-β1 expression. It has been demonstrated that NNMT-mediated methylation is an important conjugation reaction in the biotransformation of a number of drugs and xenobiotics, including pyridine and other structurally-associated compounds (18). The epigenetic silencing of TGF-β1 genes is associated with the development of pituitary adenoma (33).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also demonstrated that the upregulation of NNMT is associated with poor prognosis, advanced tumor stage, tumor cell migration and invasion (9,16,17). Although, overexpression of NNMT has been identified in gastric cancer (18), the underlying molecular mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Balb/c mice were immunized three times at a 2-week interval, each time with 100 μg of purified recombinant mouse TMAP/CKAP2. On the fifth day after the final injection, cell fusion was performed with spleen cells and sp2/O-Ag14 myeloma cells as described by Lim et al (2006). Positive clones were selected by enzyme immunoassay.…”
Section: Production Of Monoclonal Antibodiesmentioning
confidence: 99%
“…Isoelectric focusing, the first dimension of 2-DE was performed using a Multiphor II Electrophoresis System (Amersham Pharmacia, Uppsala, Sweden) as described in previous reports (Rabilloud, 1998;Choe and Lee, 2000;Gorg et al, 2000;Zuo and Speicher, 2000;Lim et al, 2006). IPG gel strips (Linear pH 4-7, 18 cm long) were rehydrated overnight (∼16 h) at room temperature in rehydration buffer (2 M thiourea, 7 M urea, 2% w/v CHAPS, 0.3% w/v DTT, 2% v/v IPG buffer and bromophenol blue).…”
Section: -De and Protein Identificationmentioning
confidence: 99%